Effect of Glycopyrolate on Nausea, Vomiting and Neonatal Outcome During Spinal Anaesthesia for Elective Caesarean Section - Amatya, Bishwo Ram; Acharya, Binita; Pradhan, Bishwas; Marhattha, Modh Nath (Medical Journal of Shree Birendra Hospital, 2016)
Introduction: Glycopyrrolate has better antisialagogue effect and does not cross placental barrier; thereby when given immediately before subarachnoid block for elective caesarean section might reduce incidence and severity of nausea and vomiting without affecting neonatal outcome. Methods: In a prospective randomized double blind placebo controlled study, sixty ASA PS I and II patients undergoing elective caesarean section at term were assigned to receive 1 ml of Inj Normal Saline IV or 1 ml (0.2 mg) of Inj Glycopyrrolate. After subarachnoid block, nausea score was assessed every 5 min during intraoperative period (before and after cord clamping), every 30 min for initial 4 hour and every 6 hour till 24 hr after surgery. Vomiting was assessed as mild (<2 episodes) and severe (>2 episodes). Apgar scores were recorded 1 min and 5 min after birth. Results:The severity of nausea was less in glycopyrrolate group than in normal saline group during intraoperative period (p value ≤ 0.001) and postoperative period (p value 0.31). During intraoperative and postoperative period, the severity of vomiting was mild in normal saline group where as in glycopyrrolate group there was no vomiting. The incidence of nausea was low in the parturient who received IV glycopyrrolate than those who received normal saline 3.33% vs. 60% (p value <0.001) during intraoperative period particularly after cord clamping 0 vs. 53.33% (p value <0.001). There was also reduced incidence of vomiting 0 vs. 13.33% (p value 0.03) during intraoperative period after cord clamping. All neonates born to the mother participating in the study had satisfactory Apgar score. Conclusions: Injection Glycopyrrolate when given as an IV premedication during spinal anaesthesia for elective caesarean section could reduce both the severity and incidence of nausea and vomiting during intraoperative period particularly after cord clamping without affecting neonatal outcome and causing side effects.